The effects of atropine and methotrimeprazine on the epinephrine-induced arrhythmias in halothane-anesthetized dogs - Teixeira Neto, Francisco J. [UNESP]; Massone, Flavio [UNESP]; Luna, Stelio P. L. [UNESP]; Camacho, Aparecido A. [UNESP]; Júnior, José Ribamar S. [UNESP]; Ishiy, Helcya M. [UNESP] (My University, 2001)
The effects of atropine and methotrimeprazine on epinephrine-induced ventricular arrhythmias were evaluated in halothane-anesthetized dogs. Ten mixed-breed dogs were assigned to 3 treatments (saline, atropine, and methotrimeprazine) in a randomized complete block design. Anesthesia was induced and maintained with halothane (1.5 minimum alveolar concentration) in oxygen. Controlled ventilation was used throughout to maintain eucapnia. Saline, atropine (0.05 mg/kg, IV) or methotrimeprazine (0.5 mg/kg, IV) were administered and, 5 minutes later the arrhythmogenic dose of epinephrine (ADE) was measured by IV infusion of progressively increasing infusion rates of epinephrine, until the ventricular arrhythmia criterion was met (at least 4 ectopic ventricular contractions (EVCs) during a 15-second period). Data were analyzed using a student's t-test for ADE values and multivariate profile analysis for heart rate (HR), arterial blood pressure (ABP), and rate pressure product (RPP). The ADE increased in atropine- and methotrimeprazine-treated groups, whereas 1 and 4 animals from these groups did not develop any ventricular arrhythmia, respectively. Epinephrine induced multiform premature ventricular contractions (PVCs) in the atropine group, whereas ventricular escape beats were observed in the control and methotrimeprazine groups. Heart rate and RPP decreased, and ABP increased at the time of ADE observation in the control group. Epinephrine infusion in the atropine group caused marked increases in HR, ABP, and RPP, which were associated with pulsus alternans in 2 animals. It was concluded that 1) the presence of cholinergic blockade influences the type of ventricular arrhythmia induced by epinephrine; 2) increased ADE values recorded following atropine administration must be cautiously interpreted, since in this situation the PVCs were associated with signs of increased myocardial work and ventricular failure; and 3) the use of a broader arrhythmia criterion (EVCs instead of PVCs) may not allow a direct comparison between ADE values, since it includes ventricular arrhythmias mediated by different mechanisms.